Hubungan Pemberian ASI Eksklusif dengan Status Gizi pada Balita Usia 6-23 bulan Di Puskesmas Kesambi Kota Cirebon - Nabilah Eka Febriyani; Jati Kusuma Wardhani; Gharini Sumbaga Narhadina (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Nutritional status in children is a critical indicator for assessing health and growth, making proper monitoring and intervention essential to prevent nutritional problems at an early age. Exclusive breastfeeding is a vital source of nutrition for infants, particularly during the first six months of life. It plays a significant role in supporting optimal growth and development while preventing nutritional issues such as malnutrition and stunting. This study aims to analyze the correlation between exclusive breastfeeding and the nutritional status of children aged 6-23 months at Kesambi Public Health Center, Cirebon City. Methods: This study used a cross-sectional design and a quantitative analytical observational method. The sample size was determined using the Slovin formula, resulting in 39 children aged 6-23 months from Kesambi Public Health Center. The Spearman rank test was used for analytical testing after conducting normality and linearity tests. Results: The majority of children aged 6-23 months had good nutritional status (32 children or 84.2%), while only 2 children (5.3%) were classified as overnourished. A strong correlation was found between exclusive breastfeeding and tparu nutritional status of children aged 6-23 months at Kesambi Public Health Center, with a p-value of 0.018 (<0.05) and a positive correlation coefficient of 0.0381. Conclusion: There is a significant correlation between exclusive breastfeeding and the nutritional status of children aged 6-23 months at Kesambi Public Health Center, Cirebon City.